STRATEGI PEMASARAN KACANG TANAH DI DESA TAGAWITI KECAMATAN ILE APE KABUPATEN LEMBATA - Sargius N. Making; Mustafa Abdurrahman; Maria Bano (Buletin Ilmiah Impas, 2022)
This research was conducted in Tagawiti Village, Ile Ape District, Lembata Regency from December 2020 to February 2021. This study aims to determine: (1) Strengths and Weaknesses of Peanut marketing; (2) Peanut Marketing Opportunities and Threats; (3) Peanut Marketing Strategy. The data collection method used in this research is the survey method. The location of the research was determined intentionally with the consideration that Tagawiti village is one of the peanut-producing villages. Determination of the number of samples used Slovin formula. The types of data collected are primary data and secondary data. The data are analyzed according to the purpose. To find out the first, second, and third purposes, the data were analyzed using SWOT analysis. The results showed that (1) The strength and weakness of peanut marketing in Tagawiti Village of Ile Ape District of Lembata Regency has an average score of 2.53 this indicates that the internal position is strong. (2) The opportunities and threats (Threats) of peanut marketing in Tagawiti Village of Ile Ape District of Lembata Regency have an average score of 2.54 this indicates that farmers respond to existing opportunities to avoid threats and (3). Marketing strategies implemented by farmers in Tagawiti Village of Ile Ape District of Lembata Regency are: a.) SO (strength-opportunity) strategy is to improve the quality and quantity of products. b.) St (strength-threat) strategy is to cooperate with the village government in sales efforts. c.) WO (Weakness-Opportunity) strategy is to improve the sales management system and promote, increase standardization and grading. d.) WT (Weakness-Threat) strategy is to improve good relations with consumers.